Physical properties of a high manganese austenitic steel Fe-30%Mn-1%C at cryogenic temperatures. (January 2023) - Jiang, Mingyue; Huang, Chuanjun; Qian, Lihe; Jia, Peng; Huang, Rongjin; Li, Laifeng
Highlights: In this work, we tested the thermal and magnetic properties of Fe30Mn1C steel from 4 K to 300 K. Fe30Mn1C steel exhibits a fully austenitic organization at low temperatures. The thermal properties of the Fe30Mn1C non-magnetic steel are comparable to those of 316 stainless steel. Abstract: In this work, the thermal and magnetic properties of a high manganese austenitic steel, Fe-30 %Mn-1 %C, were examined at cryogenic temperatures. The specific heat capacity, thermal conductivity, and coefficient of thermal expansion (CTE) of the steel were measured from 4 K to 300 K using a physical property measurement system. The magnetization of the steel from 4 K to 300 K was tested by a magnetic property measurement system. The results presented can provide a reference for the potential applications of the high manganese steel in cryogenic components.